Relationship between corporate governance and operational performance. - Lee, Jessica Yun Qian. (2008)
This study examines the relationship of corporate governance to firms’ operating performance in a Singapore context. Performance measures such as Return on Equity (ROE) and Return on Assets (ROA) were used and regressed on measures of corporate governance taken from the Singapore Code of Corporate Governance. Information obtained from www.sgx.com as well as Thomson One Banker Analytics about 265 firms listed on the Singapore Stock Exchange Index was used to generate the results. The relationship between ROE and corporate governance were insignificant. Results for the control variables yielded significant figures. Some corporate governance variables such as ‘percentage of ownership’ and ‘number of board meetings’ for ROE were close to the 0.10 significance level, however they were in the rejection region. All in all, the findings for the relationship between ROA and corporate governance showed that giving CEO some percentage ownership in the firm and having a founder in the Board lead to better operational performance in firms.